Efforts of Spiritual Leaders in The Selection of Human Resources With Islamic Character And Implications for Performance - Nadilla Aleyda Maqhfira Agustin; Zainal Arifin (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
This study aims to analyze the principal’s strategy as a spiritual leader in selecting human resources with Islamic character and its implications for teacher performance at SMA Plus Al-Azhar Jember. The study is grounded in the importance of character-based human resources as a foundation for improving the quality, integrity, and performance of educational institutions. Its central argument is that teacher recruitment should not only emphasize professional competence, but also moral integrity, Islamic values, and suitability with the school’s vision and mission. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, teachers, and students; observations of the selection process and teaching practices; and documentation studies of the school’s vision and mission, recruitment policies, and institutional programs. The data were analyzed through coding, categorization, theme identification, data presentation, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings reveal four main strategies used by the principal as a spiritual leader in selecting human resources with Islamic character. These strategies include establishing Islamic moral indicators as selection criteria, assessing the alignment between candidates’ competencies and values with the school’s vision and mission, implementing an open and merit-based selection procedure, and prioritizing integrity and moral exemplarity in prospective teachers. Empirically, these strategies contribute to the emergence of teachers who are more motivated, disciplined, sincere, responsible, and trusted as role models within the school culture. This study is limited to one Islamic senior high school context, so the findings are not intended for broad generalization. However, the results provide practical insights for principals and Islamic educational institutions in developing character-based HR selection models.